90-Day Complication Rate After the Latarjet Procedure in a High-Volume Center. Issue 14 (December 2020) - Scanlon, John P.; Hurley, Eoghan T.; Davey, Martin S.; Gaafar, Mohamed; Pauzenberger, Leo; Moran, Cathal J.; Mullett, Hannan
Background: The Latarjet procedure is indicated for patients with recurrent anterior shoulder instability, previous failed soft tissue stabilization, glenoid bone loss, or high-risk factors for recurrence, although there is still a concern with the surgical complication rates associated with the Latarjet procedure. Purpose: To evaluate the 90-day complication rate after the open Latarjet procedure in a high-volume center. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review was performed of patients who underwent an open Latarjet procedure at our institution over a 5-year period between January 2015 and December 2019. The complications, readmissions, and reoperations within 90 days were evaluated. Results: A total of 441 patients with a mean age of 23.0 ± 5.7 years was included; 97.5% of the patients were male. There were 2 intraoperative complications (0.5%): 1 coracoid fracture and 1 anaphylactic reaction to vancomycin. Overall, there were 19 postoperative complications (4.3%) in 18 patients, with 4 (0.9%) readmissions for revision surgery. Hematomas were the most common complication, occurring in 12 patients (2.7%), with 9 (2.0%) requiring a return to the operating theater during their stay for an evacuation. In those who required a readmission for a reoperation, 1 was for a hematoma requiring a washout, 2 were for irrigation and debridement of a surgical site infection, and the third was for a biceps tenodesis in a patient with severe bicipital pain. No patients had recurrence or any postoperative graft complications; additionally, there were no neurovascular complications. Conclusion: We found that in a high-volume center, the open Latarjet procedure has a low 90-day complication rate with a low revision rate. Hematomas were the most common complication experienced by patients who underwent the Latarjet procedure, while there was no recurrent instability or neurological or hardware complications reported among the 441 patients included in this study.